2014
DOI: 10.1002/2014gl060059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of particle mixtures and nozzle geometry on entrainment into volcanic jets

Abstract: Efficient turbulent entrainment causes otherwise dense volcanic jets to rise high into the atmosphere as buoyant plumes. Classical models suggest that the inflow of air is 10-15% of the axial velocity, giving predictions for the height of the plume and, in turn, the composition and structure of the resulting umbrella clouds. Crucially, entrainment is assumed independent of source geometry and mechanically unaffected by the pyroclastic mixture properties. We show that particle inertia and vent geometry act to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Valentine (1997) suggested that narrow vents and high exit velocities favour the generation of buoyant plumes. Jessop and Jellinek (2014) investigated the effect of vent geometry on entrainment characteristics of volcanic jets. They found that air entrainment is more efficient for diverging vents because of a larger surface of the jet's boundary layer due to particle inertia and trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…Valentine (1997) suggested that narrow vents and high exit velocities favour the generation of buoyant plumes. Jessop and Jellinek (2014) investigated the effect of vent geometry on entrainment characteristics of volcanic jets. They found that air entrainment is more efficient for diverging vents because of a larger surface of the jet's boundary layer due to particle inertia and trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…The critical condition separating the RSF and non‐RSF regimes and that for column collapse can be affected by other factors. The particle decoupling from gas phase can alter the entrainment properties of plumes (e.g., Cerminara, Esposti Ongaro, & Neri, ; Jessop & Jellinek, ; Jessop et al, ). The crater geometry, such as the opening angle of crater, controls the decompression‐compression processes and the exit velocity at the crater top (Carcano et al, ; Cigala et al, ; Kieffer, ; Koyaguchi & Suzuki, ; Ogden et al, ; Woods & Bower, ) and the entrainment properties (e.g., Cerminara, Esposti Ongaro, & Neri, ; Jessop & Jellinek, ).…”
Section: Discussionmentioning
confidence: 99%
“…Particles were found to augment the angular momentum of entraining eddies, forcing them to overshoot more deeply into, deform and engulf the ambient fluid. Entrainment in the flow was also enhanced for flared nozzles but it was reduced for cylindrical nozzles (Jessop and Jellinek 2014). Experiments made with linear and annular vents revealed that entrainment was reduced as the vent width became small compared to its length because the size of the entraining eddies scaled with the vent width ).…”
Section: Sustained Plinian Columnsmentioning
confidence: 97%
“…(3) Many aspects of the physics of gas-particle flows, which are ubiquitous in explosive volcanic eruptions at various solid concentrations, remain poorly understood. These include (i) the coupling between the fluid and solid phases and its consequences for the particle concentration and structure of the mixtures (e.g., Breard et al 2016, Weit et al 2019, and (ii) the interaction between these flows and their surrounding environment such as a solid substrate, a water body or the atmosphere (e.g., Jessop and Jellinek 2014). (4) Experimental work related to monitoring studies is likely to increase in the near future as it will help to better understand the relationship between observed signals and eruptive dynamics.…”
Section: Summary and Perspectivesmentioning
confidence: 99%